PENGARUH KONFLIK TIMUR TENGAH DAN STABILITAS GLOBAL DALAM PERKEMBANGAN NEGARA-NEGARA MAYORITAS MUSLIM - Madani, Ahmad Zaki; Qomar, Subaidi (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The conflict in the Middle East has become a complex global issue, affecting the political, economic, and social stability of the world. This region has high strategic value due to its position connecting three continents and its wealth of natural resources such as oil and gas. However, these resources often trigger conflicts due to various conflicting interests. This conflict has an impact on Muslim-majority countries both inside and outside the Middle East region, creating challenges such as sectarian tensions, mass migration, humanitarian crises, and economic instability. Amid these challenges, Muslim-majority countries have the potential to rise through regional cooperation, strengthening domestic economies, and sustainable development. This study aims to analyze the impact of the Middle East conflict on global stability and the development of Muslim-majority countries. By understanding the root causes thoroughly, this study offers strategic insights to manage global challenges, build solidarity, and create a more peaceful and prosperous future.